2019
DOI: 10.1021/acsanm.9b00797
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Nanoflowers Deposited on Graphene Paper as Electrode Materials for Supercapacitors

Abstract: We recently reported a simple and cost-effective green method to produce free-standing, flexible, and highly conductive electrochemically exfoliated graphene paper (GrP) for a supercapacitor application. To improve the capacitance behavior of GrP, manganese dioxide (MnO2) was electrochemically deposited on GrP with different number of MnO2 cycles. After the electrochemical deposition process, MnO2 nanoflowers were formed, which provide a fast transfer of electrolyte ions. After 10 cycles of electrodeposition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…With no surprise, the PET was a substrate to connect the electrochemically deposited MnO 2 graphene paper assembled to be the working electrode. [ 149 ] Here, the Mn precursor was also oxidized by a simple step of converting the Mn 2+ ions exhibited a very good capacitance. The bending angles were also tested up to 180° at 0.05 mA cm –2 and with the increase in current density decline in the cycles could be observed.…”
Section: Conventional Electrode Materialsmentioning
confidence: 99%
“…With no surprise, the PET was a substrate to connect the electrochemically deposited MnO 2 graphene paper assembled to be the working electrode. [ 149 ] Here, the Mn precursor was also oxidized by a simple step of converting the Mn 2+ ions exhibited a very good capacitance. The bending angles were also tested up to 180° at 0.05 mA cm –2 and with the increase in current density decline in the cycles could be observed.…”
Section: Conventional Electrode Materialsmentioning
confidence: 99%
“…The formation of rGO-MnO 2 nanostructures and their electrochemical performance have been extensively investigated and it was demonstrated that compared to the single metal-oxide, rGO/MnO 2 nanocomposites show superior electric conductivity, electric capacity and charge/ discharge efficiency for supercapacitor performance. [29][30][31][32][33][34] These characteristics make rGO/metal-oxide nanocomposites promising materials for energy applications. Considering that eld emission is geometry (shape, size, aspect ratio, alignment, and areal density of the nanostructure) and work function dependent phenomenon, well-aligned rGO/MnO 2 nanostructures is promising for enhancement of eld emission characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…GR was prepared by an electrochemical exfoliation method. 50,51 Briefly, graphite sheets (3 cm  0.5 cm) were used as electrodes. Graphite sheets (B1.5 cm length of both the anode and cathode) were dipped into 50 mL of 0.1 M PBS (pH 7) for 30 min, and +10 V was supplied using a DC power supply (Model: 2231A-30-3, Keithley, a Tektronix company, USA).…”
Section: Preparation Of Grmentioning
confidence: 99%